Dynamical analysis of Hilfer–Hadamard type fractional pantograph equations via successive approximation. Issue 1 (11th December 2019) - Vivek, D.; Shah, Kamal; Kanagarajan, K.
ABSTRACT: In this note, we consider a nonlinear pantograph equation with Hilfer–Hadamard fractional derivative. We investigate the existence and continuous dependence results by using successive approximations and generalized Gronwall inequality.